NATIONAL AND FOREIGN EXPERIENCE OF STIMULATING CIVIL SERVANTS - Alisher Nasirdinovich Juraev (Scholar Express Journals, 2022)
This article discusses what encouragement is in the public service, the specifics and essence of the concept of encouragement, as well as the problem of encouragement as a method of legal regulation and the reasons for this. The current state of legal reality has been studied, requiring the development of incentives as a special way to simplify social relations. The legal nature of normative legal acts regulating the legal status of civil servants is investigated. And also in the article examples of the international experience of civil servants are given.
Keywords: : State civil service; incentives; personal interests and behavior